Kinetically Controlled Fischer Glycosidation under Flow Conditions: A New Method for Preparing Furanosides - Masui, Seiji; Manabe, Yoshiyuki; Hirao, Kohtaro; Shimoyama, Atsushi; Fukuyama, Takahide; Ryu, Ilhyong; Fukase, Koichi (Synlett, 2019)
Kinetically controlled Fischer glycosidation was achieved under flow conditions. β-Hydroxy-substituted sulfonic acid functionalized silica (HO-SAS) was used as an acid catalyst. This reaction directly converted aldohexoses into kinetically favored furanosides to enable the practical synthesis of furanosides. After optimization of the reaction temperature and residence time, glucofuranosides, galactofuranosides, and mannofuranosides were synthesized in good yields.
Keywords: Fischer glycosidation; flow chemistry; furanosides; supported catalysis; carbohydrate; kinetically controlled reaction